THU0345 Similarities between fibromyalgia and chronic fatigue syndrome: A single disease?. (23rd January 2014) - Rivera, J.; Collado, A.; Alegre, J.; Blanch, J.; Vidal, J.; Arias, A.; Carbonel, J.
Abstract : Background: Fibromyalgia (FM) and Chronic Fatigue Syndrome (CFS) are considered two different entities. The clinical criteria used for the diagnosis do not permit to understand the true relationship between them, although they share many similar demographic and clinical aspects (1). For example: it is known that FM is a disease with extensive involvement of the nociceptive system with a significant number of tender points. However, recent studies have also shown similar findings in CFS (2). Objectives: The aim of our study is to analyze the clinical differences between these two entities in a large sample of patients. Methods: A total of 2007 patients and 398 healthy family controls were studied in different specialized units in FM and/or CFS in Spain. 1374 patients met the 1990 ACR criteria for the diagnosis of FM (women 97%, mean age 49, 3±10, 08 years), 396 patients fulfilled theFukuda criteria for CFS (women 84%, mean age 45, 44±11, 85 years) and 241 patients met both sets of criteria (women 92%, mean age 47, 23±10, 65 years). All patients and controls were studied for demographic variables, personal and family history, clinical symptoms, comorbidities, health status and standardized test sensitivities. Results: Results: The main findings are show in the table. Conclusions: The findings suggest a single process with a different stage of evolution from lower to higher severity in FM, SFC and FM-SFC, respectively. In CFS patients without FM criteria, there is a high proportion of men and have more comorbid psychopathology. Also in these patients, there are a great number of neurovegetative or immunological symptoms.There were no significant differences in the remaining variables studied, with the exception of tender points which were used as a classification criterion. References: Dedra Buchwald. Rheum Dis Clin North Am. 1996 May;22(2):219-43 Meeus M, Nijs J, Huybrechts S, Truijen S. Clin Rheumatol. 2010 Apr;29(4):393-8 Disclosure of Interest: None Declared